2017
DOI: 10.1002/2017ja024622
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Model of Precipitating Ion Oval

Abstract: In this brief technical report published maps of ion integral flux are used to constrain an empirical model of the precipitating ion oval. The ion oval is modeled as a Gaussian function of ionospheric latitude that depends on local time and the Kp geomagnetic index. The three parameters defining this function are the centroid latitude, width, and amplitude. The local time dependences of these three parameters are approximated by Fourier series expansions whose coefficients are constrained by the published ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, our practical goal is to develop an analytical model that explicitly includes plumes. One straighforward approach is Fourier expansion (e.g., Allen et al, ; Goldstein, ). However, our preliminary study found that harmonic expansion was not well suited to the very aperiodic shape of the dayside plume (Goldstein, Baker, et al, ).…”
Section: Epoch‐time‐dependent Plasmapause Modelmentioning
confidence: 99%
“…However, our practical goal is to develop an analytical model that explicitly includes plumes. One straighforward approach is Fourier expansion (e.g., Allen et al, ; Goldstein, ). However, our preliminary study found that harmonic expansion was not well suited to the very aperiodic shape of the dayside plume (Goldstein, Baker, et al, ).…”
Section: Epoch‐time‐dependent Plasmapause Modelmentioning
confidence: 99%
“…(a–c) The 30 keV polar ionospheric maps ( Λ × MLT). Dashed white curve: zero‐order ion oval latitude of H89 model (Goldstein, ; Hardy et al, ), i.e., A 0 from Appendix . (d, e, f) Differential ion flux versus MLT, nine energy bins, at H89 model latitude.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison with these TWINS J TOT curves, we extracted integral number flux from the polar maps of the H89 statistical model (Hardy et al, ; Goldstein, ); cf. Appendix .…”
Section: Resultsmentioning
confidence: 99%